A case of nontyphoidal Salmonella gastroenteritis complicated with acute acalculous cholecystitis. Issue 2 (March 2020) - Li, Chun Kit; Wong, Oi Fung; Ko, Shing; Ma, Hing Man; Lit, Chau Hung Albert
Background: Acute acalculous cholecystitis is an acute inflammation of the gall bladder in the absence of gallstones and is known to occur in those critically ill patients, including those after major surgery, patients with trauma or burn, and patients with sepsis and various infectious diseases. Salmonella infection is one of the commonest food-borne illnesses. Although cholecystitis is a well-reported complication of typhoidal Salmonella infection, it is rarely reported in nontyphoidal Salmonella infection.Case Presentation: We report a case of nontyphoidal Salmonella infection complicated by acute acalculous cholecystitis. Prompt diagnosis was made and the patient was recovered after percutaneous cholecystostomy.Conclusion: Acute acalculous cholecystitis is a rare, but potentially lethal, complication of Salmonella infection. The clinical presentation is often subtle; therefore, a high degree of suspicion should be maintained in managing patients with Salmonella infection and ongoing sepsis.